Pengaruh Budaya Organisasi, Kompetensi Karyawan dan Komitmen Organisasi Terhadap Kinerja Karyawan Pada PT Raja Pasar Abadi - Laksmi Sito Dwi Irvianti; Lisna Hadinata Liusman (Jurnal Ekonomi, Manajemen dan Perbankan (Journal of Economics, Management and Banking), 2016)
This research was conducted at PT Raja Pasar Abadi. The purpose of this study was to determine whether there is an influence of Organizational Culture, Employee Competencies, and Organizational Commitment on Employee Performance. Data were obtained through interviews and questionnaires to all employees of PT Raja Pasar Abadi totaling 64 people as respondents. The analytical method used was a simple regression analysis and multiple regression analysis by using IBM SPSS 20 for data processing. The results of this research showed that organizational culture, employee competencies, and organizational commitment have a significant effect on employee performance, partially and simultaneously.